2018
DOI: 10.5194/essd-2018-51
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mediterranean Sea climatic indices: monitoring long term variability and climate changes

Abstract: Abstract. We present a new product composed of a set of thermohaline climatic indices from 1950 to 2015 for the Mediterranean Sea such as decadal temperature and salinity anomalies, their mean values over selected depths, decadal ocean heat and salt content anomalies at selected depth layers as well as their long times series. It is produced from a new high-resolution climatology of temperature and salinity on a 1/8• regular grid based on historical high quality in situ observations. Ocean heat and salt conten… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…Also, results revealed that the highest rate of increase of the MATA linear trends was +0.02°C/yr (100 m level), while all other rates varied between +0.001 and +0.005°C/yr. This range is in agreement with that concluded by Iona et al (2018) for the Levantine Basin.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Also, results revealed that the highest rate of increase of the MATA linear trends was +0.02°C/yr (100 m level), while all other rates varied between +0.001 and +0.005°C/yr. This range is in agreement with that concluded by Iona et al (2018) for the Levantine Basin.…”
Section: Discussionsupporting
confidence: 93%
“…The Mediterranean is known to play an indirect role in the water formation processes and thermohaline circulation in the North Atlantic with its very saline outflow to the Atlantic through the Strait of Gibraltar (Reid 1979, Lozier et al 1995, Bethoux et al 1998. In recent decades, the Mediterranean Sea has examined rapid change of increase in its temperature and salinity (Rohling and Bryden 1992, Schroeder et al 2017, Iona et al 2018, reflecting the global general warming trend (Levitus et al 2012). During the period between late 1980s and mid-1990s, the circulation pattern the eastern Mediterranean basin practiced a remarkable change from the surface to the deep layers (Iona et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, an effort towards the development of climate indices and the improvement of longterm times series by in situ observations is of importance, for both open and coastal areas. Both heat and saline content are a primer (e.g., Iona et al [2018]), but estimates of stratification from the water-column also have to be included to be compared to the observations in the upper 200 m during the recent decades (e.g., Guancheng et al [2020]) and to separate the roles of thermal and saline contents. The Mediterranean Sea is an important zone for attempting projections [Giorgi & Lionello, 2007], as it has been identified as a major 'hotspots' for exhibiting the effects of climate changes Giorgi [2006].…”
Section: Introductionmentioning
confidence: 99%
“…Many publications establishing which are the factors that condition the SSS in the Mediterranean and which impact have for the function of costs of this mode of transport [ 4 , 5 ]; generally, these articles analyse its efficiency and sustainability [ 6 , 7 ]. However, some knowledge on climatology and meteorology is key to understand the case that occupies us; the climatology of the Mediterranean has been amply studied by numerous authors [ 8 – 10 ] and continues being a very present element in the recent academic production [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%